Disease-related malnutrition in congenital 27 heart disease: what is the risk and impact on patient’s outcomes? - Noormanto (Indonesian Nutrition Association, 2022)
Congenital heart disease (CHD) is the most common congenital anomaly in newborn babies. Malnutrition is common in children with congenital heart disease and may contribute to adverse outcomes. Malnutrition in children with CHD has been link to increased morbidity and mortality. Nutritional assessment and intervention before and after surgery is recommended to improve poor outcomes. This review aims to provide information about common CHD in children and nutrition pre- and post-operative cardiac surgery.